Kinesiographic study of complete denture movement related to mucosa displacement in edentulous patients. - Compagnoni, Marco Antonio [UNESP]; Souza, Raphael Freitas de; Leles, Cláudio Rodrigues (FapUNIFESP (SciELO), 2003)
The mucosa that covers the residual ridges of edentulous patients may present some distortion or displacement when occlusal loading is applied in complete dentures. This distortion and movement of the denture can result in acceleration of residual ridge resorption and loss of retention and stability. The aim of this study was to analyze the pattern of upper complete denture movement related to underlying mucosa displacement. A sample of 10 complete denture wearers was randomly selected, which had acceptable upper and lower dentures and normal volume and resilience of residual ridges. The kinesiographic instrument K6-I Diagnostic System was used to measure denture movements, according to the method proposed by Maeda et al.7, 1984. Denture movements were measured under the following experimental conditions: (A) 3 maximum voluntary clenching cycles and (B) unilateral chewing for 20 seconds. The results showed that under physiological load, oral mucosa distortion has two distinct phases: a fast initial displacement as load is applied and a slower and incomplete recovery when load is removed. Intermittent loading such as chewing progressively reduces the magnitude of the denture displacement and the recovery of the mucosa is gradually more incomplete.
Keywords: aged; dental care; denture; female; human; kinesiology; male; mastication; methodology; middle aged; mouth disease; mouth mucosa; pathophysiology; physiology; tooth occlusion; tooth radiography; Aged; Dental Stress Analysis; Denture Retention; Denture, Complete; Female; Humans; Jaw Relation Record; Kinesiology, Applied; Male; Mastication; Middle Aged; Mouth Mucosa; Mouth, Edentulous; Vertical Dimension